1999
DOI: 10.1063/1.123867
|View full text |Cite
|
Sign up to set email alerts
|

Defect-related infrared photoluminescence in Ge+-implanted SiO2 films

Abstract: SiO 2 films with Ge+ implantation at an energy of 60 keV and a dose of 1×1016 cm−2, followed by annealing at different temperature, exhibit a broad infrared photoluminescence (PL) at room temperature under an excitation of the 514.5 nm line of Ar+ laser. With increasing the annealing temperature, the intensity of the infrared PL band decreases, its full width at half maximum increases, and its energy redshifts. Spectral analysis and some experimental results from Raman scattering, electron spin resonance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 24 publications
0
39
0
2
Order By: Relevance
“…In all samples, we found that d and s increase with annealing temperature. In the sample annealed at 1100 ± C, d and s abruptly increase to ϳ9.8 and 6.18 nm, respectively, but no micropin holes were observed in the SiO 2 network [19]. This indicates that the Er existence is beneficial to growth of Si crystallites and formation of dense SiO 2 .…”
mentioning
confidence: 73%
“…In all samples, we found that d and s increase with annealing temperature. In the sample annealed at 1100 ± C, d and s abruptly increase to ϳ9.8 and 6.18 nm, respectively, but no micropin holes were observed in the SiO 2 network [19]. This indicates that the Er existence is beneficial to growth of Si crystallites and formation of dense SiO 2 .…”
mentioning
confidence: 73%
“…Several studies on the optical properties of Ge nanocrystals (NCs) embedded in Si oxide films and on their photoluminescence (PL) mechanism have been reported. [1][2][3] Recently, violet-blue and blue PL emission have been reported from Ge implanted SiO 2 layers and there exist controversy regarding the origin of the violetblue PL emission. 4 5 Rebohle et al 6 reported a strong blueviolet PL and electroluminescence from Ge-implanted and Si-implanted SiO 2 layer and they attributed the observed PL to neutral oxygen vacancies in SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lattice mismatch of 4% between the Si and Ge, and consequently, band alignment is modified by the strain. Ge NCs capped with thin Si shell are also promising because Si acts as a protective coating, eliminating formation of the GeO oxide layer, 19 source of emissive defect centers 20,21 and/or emission quenching. 22 Type-II heterostructures are in general interesting for photodetectors and memory applications 19 due to lowered rates of optical transitions, as spatially separated electron and hole recombine less efficiently.…”
Section: Introductionmentioning
confidence: 99%